Checking and challenging your rateable value : The Government's proposals to improve transparency in the business rates valuation and formal challenge system.: The Government's proposals to improve transparency in the business rates valuation and formal challenge system. (December 2013) - Great Britain., Department for Communities and Local Government,
No abstract available